Vertebrate mixed pollination system in Encholirium spectabile: A bromeliad pollinated by bats, opossum and hummingbirds in a tropical dry forest. (February 2016) - Queiroz, J.A.; Quirino, Z.G.M.; Lopes, A.V.; Machado, I.C.
Abstract: Mixed or generalized pollination systems tend to establish when the benefits of the pollination services to the plant are higher than the losses. In this context, selective pressures are likely to favor the presence of floral traits adequate to a variety of pollinators. In this paper, we document the pollination ecology of Encholirium spectabile, focusing on nectar production pattern, and on the frequency, behavior and effectiveness of day- and nighttime pollinators. We have addressed two main questions: (1) Are the flowers traits of E. spectabile favorable to a mixed pollination system? and (2) Do diurnal and nocturnal visitors behave as effective pollinators? Nectar traits of E. spectabile were similar to other chiropterophilous and ornithophilous bromeliads, and the main pollinators were exclusively vertebrates, both nocturnal (bats and opossum), and diurnal (hummingbirds and Passeriformes). Despite E. spectabile is primarily chiropterophilous, its flowers were open during the entire day and night, with continuous nectar production, what is favorable to the occurrence of a mixed pollination system, involving a unique richness of vertebrate as pollinators of a single plant species. This strategy has assured to E. spectabile high frequency of visits along flowering with high reproductive success. Highlights: Encholirium spectabile is primarily chiropterophilous. Floral traits of E. spectabile favor the occurrence of a mixed pollination system. The main pollinators of E. spectabile were nocturnal and diurnal vertebrates. Opossum pollination in Bromeliaceae and also in Caatinga vegetation is novelty. Mixed pollination has assured to E. spectabile high reproductive success.